2021
DOI: 10.1108/bfj-10-2020-0916
|View full text |Cite
|
Sign up to set email alerts
|

Emotional or logical: reason for consumers to buy organic food products

Abstract: PurposeThe purpose of this paper is to understand, among the emotional, practical and logical factors, which factor is more critical while consumers buy organic food products, mostly fruits and vegetables.Design/methodology/approachA self-administered questionnaire survey approach was used to provide a deeper insight into the reasons for consumers to buy organic fruits and vegetables (OF&V). A total of 632 valid questionnaires were obtained, yielding a response rate of 79%.FindingsHealth is a functional/pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 79 publications
(119 reference statements)
2
24
0
Order By: Relevance
“…The researchers recognized that willingness to take the effort is a less researched area in determining to purchase organic food (Jose and Kuriakose, 2021). This study measures food effort using a scale from these studies (Jose and Kuriakose, 2021;Lichtenstein and Burton, 1989). Following is the proposed hypothesis.…”
Section: Food Effort and Intention To Purchase Organic Foodmentioning
confidence: 99%
See 3 more Smart Citations
“…The researchers recognized that willingness to take the effort is a less researched area in determining to purchase organic food (Jose and Kuriakose, 2021). This study measures food effort using a scale from these studies (Jose and Kuriakose, 2021;Lichtenstein and Burton, 1989). Following is the proposed hypothesis.…”
Section: Food Effort and Intention To Purchase Organic Foodmentioning
confidence: 99%
“…The effort, also known as non-monetary costs, significantly influences the intention to buy organic food (Hoffmann and Schlicht, 2013). Usually, the customers are not ready to use extra time and effort to buy organic food (Jose and Kuriakose, 2021). The researchers recognized that willingness to take the effort is a less researched area in determining to purchase organic food (Jose and Kuriakose, 2021).…”
Section: Food Effort and Intention To Purchase Organic Foodmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Dorce et al (2021) found that the relationship between the cost of purchasing organic foods and consumers' intentions is not well defined in prior research. Some studies found that the relatively higher price of organic products is not a barrier (Ahangarkolaee and Gorton, 2020;Jose and Kuriakose, 2021;Massey et al, 2018), while others report opposite findings. For instance, Liang (2016) showed that some consumers prefer to purchase lower-priced food products rather than the higher-priced organic ones.…”
Section: Cost Perceptionsmentioning
confidence: 99%